Legal Aspects of Central Bank Digital Currency : Central Bank and Monetary Law Considerations. (Washington, D.C. : International Monetary Fund, 2020)
This paper analyzes the legal foundations of central bank digital currency (CBDC) under central bank and monetary law. Absent strong legal foundations, the issuance of CBDC poses legal, financial and reputational risks for central banks. While the appropriate design of the legal framework will up to a degree depend on the design features of the CBDC, some general conclusions can be made. First, most central bank laws do not currently authorize the issuance of CBDC to the general public. Second, from a monetary law perspective, it is not evident that 'currency' status can be attributed to CBDC. While the central bank law issue can be solved through rather straithforward law reform, the monetary law issue poses fundmental legal policy challenges.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet